A general case of the commutativity degree of nilpotent p-groups of class two - Sarmin, Nor Haniza (2012)
Given a finite group, the commutativity degree of the group is defined as the probability that two elements of the group, chosen randomly with replacement, commute. The commutativity degree can be considered as a special case of a more general probability which is the probability that the commutator of two group elements is equal to a given element in the group. This research focuses on the finite p-groups of nilpotency class two. Some basic concepts and results on the general case of the commutativity degree are presented.